Immune‐dysregulation harnessing in myeloid neoplasms - Mohammad Jafar Sharifi; Ling Xu; Nahid Nasiri; Mehnoosh Ashja‐Arvan; Hadis Soleimanzadeh; Mazdak Ganjalikhani‐Hakemi (Cancer Medicine)
Abstract Myeloid malignancies arise in bone marrow microenvironments and shape these microenvironments in favor of malignant development. Immune suppression is one of the most important stages in myeloid leukemia progression. Leukemic clone expansion and immune dysregulation occur simultaneously in bone marrow microenvironments. Complex interactions emerge between normal immune system elements and leukemic clones in the bone marrow. In recent years, researchers have identified several of these pathological interactions. For instance, recent works shows that the secretion of inflammatory cytokines such as tumor necrosis factor‐α (TNF‐α), from bone marrow stromal cells contributes to immune dysregulation and the selective proliferation of JAK2V617F+ clones in myeloproliferative neoplasms. Moreover, inflammasome activation and sterile inflammation result in inflamed microenvironments and the development of myelodysplastic syndromes. Additional immune dysregulations, such as exhaustion of T and NK cells, an increase in regulatory T cells, and impairments in antigen presentation are common findings in myeloid malignancies. In this review, we discuss the role of altered bone marrow microenvironments in the induction of immune dysregulations that accompany myeloid malignancies. We also consider both current and novel therapeutic strategies to restore normal immune system function in the context of myeloid malignancies.